Practical homicide investigation checklist and field guide - Geberth, Vernon J. (CRC series in practical aspects of criminal and forensic investigations., 2014)
The Checklist Approach to Homicide InvestigationThe Homicide Crime SceneIntroductionThe Patrol Officer's Duties First Officer's Duties upon Arrival Patrol Officer Establishing the Crime SceneThe First Officer Initiates the Homicide Investigation The Patrol Officer's Checklist The Preliminary Investigation at the SceneThe Detectives Prior to Leaving for the Crime Scene, Instruct Patrol to Arrival at the Scene The Investigative Checklist Documentation of the Initial Report Duties of the Detective Supervisor upon Arrival at the Scene Specific Investigative Duties at the SceneThe Suspect in Custody Evaluation of the Suspect's Demeanor and Mental Capacity Obtaining a Dying Declaration Suicide Investigation Three Investigative Considerations in Determining the Manner of Death (Homicide or Suicide) Suicide Notes Suicide Checklist Psychological Aspects Final Exit Suicides Investigative Checklist for Final Exit Cases The Plastic Bag Suicide By Cop Scenarios Some Suicide Indicators Autoerotic FatalitiesInvestigative ConsiderationsAutoerotic Checklist: Determining the Involvement of Sexual Asphyxia Investigative Fatal Fires Checklist Investigative ConsiderationsThe Fire Incident Suspicious Designation: General Determination Factors Maintenance of the Fire Crime Scene Investigation at the Scene Determination of Arson Sudden Infant Death Syndrome (SIDS) Investigative Checklist Munchausen Syndrome by Proxy Warning Signs Crime Scene Documentation Documentation of Crimes Scene Photographs Recommended Crime Scene Photographs Photographs of Deceased SubjectsVideotape ProtocolTaping Protocol ChecklistDocumentation of the Crime Scene SketchThe Title Block Formulating the Search Examination of the Outdoor Crime Scene Investigative Questions Examination of the Body at the SceneThe Wound Chart Gunshot Wounds Cutting Wounds Blunt Force Injuries Asphyxial Deaths Recommendations and Guidelines for Proper Death.